Utilización de nitrógeno no proteico nnp en alimentación de bovinos en pastoreo - Castillo Chamba, William René (2008)
The current research on the Use of Nitrogen without protein in feeding pasture bovine was carried out in the experimental farm Pagua of the University of Machala, in the El Oro Province, during the months of July and August of 2008, with the following objectives: 1. To use urea as a source of nitrogen without protein in the feeding of pastured bovine; 2. To determine the increment of weight using different levels of urea. 3. To establish the costs of production of meat in the treatments. The animals used were 24 Brown mestizo swiss cows between 18 – 19 months of age with an initial average weight of 308,25 kilograms for the females and 308,16 for the males, divided into four lots made up of three females and three males in each, standardized for age and weight and assigned at random to four treatments: only pasture, pasture + urea 2%, pasture + urea 3%, pasture + urea 4%. For the effect they were used in successive shape herdsmen of Janeiro, Saboya, Brachiaria and German. The duration of experimentation was 60 days including the period of becoming used to the consumption of urea, when they arrived in the pasture the animals were given 1 kg of polvillo mixes, molasses, salt and pearly urea, the same one that was placed in the existing cement troughs in the farm. The final weight and the gain of weight in kilograms were of 329,33 and 21,33; 339, and 31,83; 339,83 and 31,17; 344,33 and 36,00 in the females and in the males of 333,67 and 25,00; 344,50 and 36,50; 341,00 and 33,00; 336,33 and 28,33 for the treatments of only pasture, however pasture + urea 2%, pasture + urea 3%, pasture + urea 4%, didn't show statistic al difference between the treatments or according to the sex. The biggest profitability from the economic point of view was obtained in the treatment of pasture + urea 2% with $3172,86; followed by: pasture + urea 3% with $3151,99; pasture + urea 4% with $3149,12 and only pasture with $3160,20.